Phoenix dactylifera L. Fruit Induces Cell Proliferation of A2780, A172 and HFFF2 Cell Lines: Activatory effects of date on cell proliferation - Ali Ramazani; Marzieh Mashhadi; Fatemeh Balaghi; Mohammad Kamalinejad; Farshad H. Shirazi; Mahdi Tavakolizadeh; Maryam Noubarani; M ohammad Reza Eskandari (Iranian Journal of Pharmaceutical Sciences, 2016)
Dates fruit has been used as staple food in the Middle East for thousands of years and various types of dates are found worldwide. Dates and their constituents show various roles in diseases prevention and treatment through anti-oxidant, anti-inflammatory, and anti-bacterial activity. In the present study we investigated the activities of aqueous and n-hexane extracts of Phoenix dactylifera L. fruit at various concentrations on A2780, A172 and HFFF2 cell lines proliferation by means of MTT (3-4, 5-dimethylthiazol-2-yl-2, 5 diphenyl tetrazolium bromide) assay. Aqueous and n-hexane extracts of date showed activatory effects on the cell lines and increased cell proliferation in a dose dependent manner. It has been previously reported that dates fruit possesses anticancer and antimutagenic effects. These disagreements can be explained by differences in cell line properties, type of date fruits, and different solvents in the extracts. However, further investigations are needed to clarify the exact role of date in cell proliferation and cancer. In addition, n-hexane extract acted more powerful than the aqueous extract in increasing the cell lines proliferation. Therefore, it can be concluded that the active components that are responsible for the activatory effects are present in the n-hexane extract.